The Effect Of Auditor Experience And Audit Fees On Fraud Detection With Professional Skepticism As A Moderating Variable - Nabilah Fathurohmah; Wasfini (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to examine how Auditor Experience and Audit Fee affect Fraud Detection. As well as assessing how Professional Skepticism moderates Auditor Experience and Audit Fee on Fraud Detection. Design/methodology/approach – This study uses quantitative research methods, using primary data collected from a population of 130 from several financial services sector companies registered in the Bekasi City area. Data analysis was performed using Partial Least Square (PLS) software with Moderated Regression Analysis. Findings – The results of this study found that Auditor Experience has a negative and insignificant effect on Fraud Detection, Audit Fee has a positive and significant effect on Fraud Detection, Skepticism strengthens the relationship between Auditor Experience and Fraud Detection, Professional Skepticism does not strengthen Audit Fee on Fraud Detection. Research limitations/implications – In this assessment of fraud detection, where this research is a research that has been little discussed by previous researchers, which discusses the effect of audit fees on fraud detection.